Faktor Penentu Nilai Perusahaan: Peran Ukuran Perusahaan dan Profitabilitas di Indonesia - Nasihin, Ihsan; Purwandari, Dian; Ardiansyah, Hendri Nur; Kartika, Erawati; Prawatiningsih, Desty (Gorontalo Accounting Journal, 2025)
This study aims to analyze the influence of company size and profitability on company value in property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 period. The study used a quantitative method with multiple linear regression analysis. Secondary data from the company's financial statements is used, including total assets, Return on Assets (ROA), and Price to Book Value (PBV). Classical assumption tests are performed to ensure the feasibility of the model, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results show that company size and profitability have a positive and significant influence on the value of the company both partially and simultaneously. The Adjusted R² coefficient of 52.1% shows that these two variables together are able to explain the variation in the company's value. This research emphasizes the importance of company management in improving operational scale and efficiency to create higher value for shareholders.